Safety analysis in the calculation of overlay thicknesses for flexible pavements - Zaldívar Serrano, Ernesto (2025)
The use pd the concept of security of security is analyzed in the overlay design of flexible pavements; the option more used in the Latin American countries is the concept of reliability, especially the one used in the method AASTHO, guides of 1986 and 1993. In the method, the level of reliability expressed in percent is used and the general standard deviation associated with the data of the project. In these guides recommendations are made on the use of this general standard deviation and when the designers don’t have full knowledge, it can lead to designs over or sub dimensioned. In this research, a procedure is proposed for the calculation of the general standard deviation of the project, which allows using more rational security factors.